Therapeutic Potential of Topical Metformin in Diabetic Wound Healing: Preclinical Mechanistic Insights - Citra Safitri Wirman; Darmawi; Benni Iskandar (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Diabetic wounds remain one of the most challenging complications of diabetes mellitus, largely due to persistent inflammation, oxidative stress and impaired tissue regeneration. These conditions contribute to delayed healing and increase the risk of infection and amputation. In recent years, topical metformin has gained attention as a potential therapeutic option to improve wound healing outcomes. This review aims to summarize current preclinical evidence on the effectiveness of topical metformin, with a particular focus on its underlying molecular mechanisms. Evidence from experimental studies suggests that topical metformin can accelerate wound healing through several interconnected pathways, including activation of AMP-activated protein kinase (AMPK), suppression of NF-κB–mediated inflammation, reduction of reactive oxygen species (ROS) and regulation of extracellular matrix remodeling. Moreover, the advancement of sophisticated delivery technologies, such as hydrogels and nanocomposites has significantly augmented the localized therapeutic efficacy of metformin. The evidence suggests that topical metformin may be a new way to treat diabetic wounds. However, additional rigorously planned studies and clinical trials are necessary to validate its safety, enhance its formulation and facilitate its clinical use. Keywords : AMPK activation; Diabetic wound; Inflammation; Preclinical evidence; Topical metformin